Feasibility of Transnasal Esophagogastroduodenoscopy (TNE) in an Emergency Situation - Mori, Akihiro; Fushimi, Nobutoshi; Ohashi, Noritsugu; Yoshida, Atsuo; Nozaki, Masashi (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2012)
Aims: Transnasal esophagogastroduodenoscopy (TNE) has been reported to be less stressful to the cardiovascular system and tolerable in patients without sedation. Because of this, we considered that TNE may be safe and useful in emergency endoscopy. We assessed the feasibility, diagnostic capability and safety of emergency TNE (e-TNE) in the study. Methods: We performed TNE prospectively and sequentially under non-sedation in patients having an episode of upper gastrointestinal bleeding, and evaluated diagnostic capability and cardiovascular responses during e-TNE. Results: Emergency endoscopies were performed in 210 patients, among whom we could confirm the diagnosis in 203 patients (97%) (including 80 peptic-ulcer patients) with e-TNE. Endoscopic hemostases were performed in 58 patients, in which we accomplished the first hemostasis in 40 patients (69%) with TNE alone with an epinephrine injection. There were no significant cardiovascular changes or major complications during e-TNE. The rebleeding rate of e-TNE was 8% (3 patients). Conclusion: TNE in emergency cases appears to be sufficiently feasible and safe with good diagnostic capability. The procedure may be reasonable as an alternative for first look in emergency endoscopy.